ANALISIS PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN MINAHASA UTARA - BASTIAN GUSTIANO RANDANG; WILLIAM A. AREROS; SONNY KAPARANG (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract : Reception and Contributions PBB-P2 is very important in supporting regional revenue.With the enforcement of the regulations in force in the region, it can provide an opportunity for local governments to carry out development based on the acceptance ofLocal Revenue. This study aims to, know and analyze the contribution of PBB-P2 on revenue in North Minahasa Regency in 2013 until 2015.The data collection technique used is the type of qualitative and quantitative data, primary and secondary data sources, observation, list of questions (questionnaire), the study documents.While the analytical technique used is the technique of contribution analysis.North Minahasa Regency is a new expansion area is carved out of Minahasa, Minahasa estimated first been inhabited by humans for thousands of years before Christ.The results of data analysis showed that (1) Total realized PBB-P2 in North Minahasa Regency annually increased,(2) The contribution of the PBB-P2 to the regional income shows, PBB-P2 has a good contribution to local revenues North Minahasa Regency that tax revenue from the sector PBB-P2 reliable as a source of revenue. Keywords: Acceptance of PBB-P2, Contributions, Local Revenue